RAFT Polymerization of an Intrinsically Stretchable Water-Soluble Block Copolymer Scaffold for PEDOT - Kayser, Laure V. (Chem Mater, 2018)
Despite the common association of π-conjugated polymers with flexible and stretchable electronics, these materials can be rigid and brittle unless they are designed otherwise. For example, low modulus, high extensibility, and high toughness are treated as prerequisites for integration with soft and biological structures. One of the most successful and commercially available organic electronic materials is the conductive and brittle polyelectrolyte complex poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS). To make this material stretchable, additives such as ionic liquids must be used. These additives may render the composite incompatible with biological tissue. In this work, we describe the synthesis of an intrinsically stretchable variant of the conductive polymer PEDOT:PSS that is free of additives. The approach involves the synthesis of a block copolymer comprising soft segments of poly(polyethylene glycol methyl ether acrylate) (PPEGMEA) and hard segments of poly(styrene sulfonate) (PSS) using a reversible addition-fragmentation chain transfer (RAFT) polymerization. Subsequently, we used the newly synthesized ionic elastomer PSS-b-PPEGMEA as a matrix for the oxidative polymerization of EDOT. The resulting polyelectrolyte elastomer, PEDOT:PSS-b-PPEGMEA, can withstand elongations up to 128% and has a toughness up to 10.1 MJ m(−3). While the polyelectrolyte elastomer is not as conductive as the commercial material, the toughness and extensibility are each more than an order of magnitude higher. Moreover, the electrical conductivity of the polyelectrolyte elastomer exhibits minimal decrease with strain within the elastic regime. We then compared the block copolymer to physical blends of PEDOT:PSS and PPEGMEA. The blend material had a much lower failure strain of only 38% and a maximum toughness of 4.9 MJ m(−3). This approach thus emphasizes the importance of the covalent linking of the PSS and PPEGMEA blocks. Furthermore, we demonstrate that the conductivity of scratched films can be restored upon exposure to water.